2023
DOI: 10.3390/foods12183472
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Differences between Viable but Nonculturable and Recovered Lacticaseibacillus paracasei Zhang

Huiying Wang,
Yuhong Zhang,
Lixia Dai
et al.

Abstract: The fermentation process can be affected when the starter culture enters the viable but nonculturable (VBNC) state. Therefore, it is of interest to investigate how VBNC cells change physiologically. Lacticaseibacillus (L.) paracasei Zhang is both a probiotic and a starter strain. This study aimed to investigate the metabolomic differences between VBNC and recovered L. paracasei Zhang cells. First, L. paracasei Zhang was induced to enter the VBNC state by keeping the cells in a liquid de Man–Rogosa–Sharpe (MRS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Metabolomic studies have revealed significant differences between VBNC and recovered cells, particularly in Lacticaseibacillus paracasei Zhang, a probiotic and starter strain. Levels of specific amino acids like L-cysteine, L-alanine, L-lysine, and L-arginine notably increased in revived cells, suggesting altered physiology in the VBNC state ( Wang et al, 2023 ).…”
Section: Alternatives In Viability Definitionmentioning
confidence: 99%
“…Metabolomic studies have revealed significant differences between VBNC and recovered cells, particularly in Lacticaseibacillus paracasei Zhang, a probiotic and starter strain. Levels of specific amino acids like L-cysteine, L-alanine, L-lysine, and L-arginine notably increased in revived cells, suggesting altered physiology in the VBNC state ( Wang et al, 2023 ).…”
Section: Alternatives In Viability Definitionmentioning
confidence: 99%